The Effectiveness of Lesson Study in Improving the Quality of Science Learning in Secondary Schools - Rahmadhea, Savira; Hasan, Fadhilah; Kumar, Rajesh (Journal Sains and Education, 2025)
Education plays a vital role in the progress of a country, with science learning at the secondary school level being the key to developing creative and adaptive human resources to global developments. However, the implementation of science learning in schools still faces various challenges, such as limited resources, conventional methods, and lack of technology utilization. To overcome this, innovation in teaching methods and continuous training for educators are important. One approach that has proven effective is Lesson Study, which emphasizes collaboration between teachers in planning, implementing, and reflecting on learning. This approach helps improve student understanding through more structured and interactive learning and develops critical thinking and problem-solving skills. Although it has been implemented in various countries, including Indonesia, the implementation of Lesson Study still faces obstacles, such as time constraints and lack of institutional support. This study aims to evaluate the effectiveness of Lesson Study in improving the quality of science learning in secondary schools using the literature review method. The data sources used come from research journals, scientific articles, research reports, and dissertations related to Lesson Study and science learning. Data analysis was carried out descriptively-qualitatively with a thematic synthesis approach to identify patterns and relationships between sources. The results of the study indicate that the implementation of Lesson Study is effective in improving the quality of science learning, with increased student understanding and teacher competence in designing and evaluating learning. However, the success of implementing this model depends on institutional support, including flexible time scheduling and policies that support collaboration between teachers. This study is expected to provide a comprehensive picture of the implementation of Lesson Study and recommendations for optimizing its implementation in improving the quality of science education in secondary schools